1983
DOI: 10.1002/cber.19831161208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α‐Cyanoenamines by Cyanation of α‐Bromoimmonium Bromides and Dehydrobromination of β‐bromo‐α‐(dialkylamino)nitriles

Abstract: The reaction of a-bromoimmonium bromides 4 with potassium cyanide in dimethylformamide gave rise to P-bromo-a-(dia1kylamino)nitriles 5, which were dehydrobrorninated in various basesolvent systems to afford (E)-and (Z)-a-cyanoenamines 2. An adaption of a previously published preparation of a-cyanoenamines starting from aldehydes oia enamines led to an improved, efficient and fast synthesis of the title compounds. Synthese von a-Cyanenaminen durch Cyanierung von a-Bromimmonium-bromiden und Dehydrobromierung von… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
(3 reference statements)
0
7
1
1
Order By: Relevance
“…More recently, Hayashi and co-workers have reported a related enantioselective α-hydroxymethylation of aldehydes catalyzed by the related 3,5-bistrifluoromethylaryl prolinol in comparable yields and enantioselectivity, but with the opposite sense of asymmetric induction . In contrast to our protocol, where the enantioselectivtiy is apparently controlled by the steric bulk of the diaryl- and trialkylsilyloxy- substituent of the prolinol, the catalyst systems employed by Córdova and Hayashi apparently impart enantioselectivity through hydrogen bonding with the carboxylic acid or alcohol functionality of the catalyst serving to orient the formaldehyde electrophile syn to the α substituent of the proline in the transition state. , …”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…More recently, Hayashi and co-workers have reported a related enantioselective α-hydroxymethylation of aldehydes catalyzed by the related 3,5-bistrifluoromethylaryl prolinol in comparable yields and enantioselectivity, but with the opposite sense of asymmetric induction . In contrast to our protocol, where the enantioselectivtiy is apparently controlled by the steric bulk of the diaryl- and trialkylsilyloxy- substituent of the prolinol, the catalyst systems employed by Córdova and Hayashi apparently impart enantioselectivity through hydrogen bonding with the carboxylic acid or alcohol functionality of the catalyst serving to orient the formaldehyde electrophile syn to the α substituent of the proline in the transition state. , …”
Section: Introductioncontrasting
confidence: 60%
“…To investigate the feasibility of the foregoing catalytic cycle, we began with the reaction of the preformed enamine 5 , derived from pyrrolidine and isovaleraldehyde with varying amounts of 37% aq formaldehyde (formalin) . Our preliminary experiments demonstrated that use of ∼3.0 equiv of formalin in a variety of solvents followed by the reduction of crude products with sodium borohydride (NaBH 4 ) provided substantial amounts of allylic alcohol 6 rather than the desired α-hydroxymethylation product 7 accompanied by trace amounts of alcohol 8 derived from the self-condensation of isovaleraldehyde followed by dehydration (1.5:1:trace of 6 : 7 : 8 ) .…”
Section: Resultsmentioning
confidence: 99%
“…The overall result of this stepwise reaction corresponds to fluorocyantion of the CC bond. It should be pointed out that in the literature addition reactions of cyanogen fluoride to alkenes have not been reported …”
mentioning
confidence: 99%
“…There are also other examples where the resulting 2-amino-3halopropiononitriles 10 were subjected to dehydrohalogenation to give the corresponding 1-cyanoenamines 2a, including those with the unsubstituted, 39 mono- 40 or disubstituted amino group. 41,42 For these reactions, Et 3 N 32 ± 36, 39 ± 41 or NaOH 31 are the reagents of choice.…”
Section: Introductionmentioning
confidence: 99%